Bio-imaging with the helium-ion microscope: A review - Schmidt, Matthias; Byrne, James M.; Maasilta, Ilari J. (Beilstein Journal of Nanotechnology, 2021)
Scanning helium-ion microscopy (HIM) is an imaging technique with sub-nanometre resolution and is a powerful tool to resolve some of the tiniest structures in biology. In many aspects, the HIM resembles a field-emission scanning electron microscope (FE-SEM), but the use of helium ions rather than electrons provides several advantages, including higher surface sensitivity, larger depth of field, and a straightforward charge-compensating electron flood gun, which enables imaging of non-conductive samples, rendering HIM a promising high-resolution imaging technique for biological samples. Starting with studies focused on medical research, the last decade has seen some particularly spectacular high-resolution images in studies focused on plants, microbiology, virology, and geomicrobiology. However, HIM is not just an imaging technique. The ability to use the instrument for milling biological objects as small as viruses offers unique opportunities which are not possible with more conventional focused ion beams, such as gallium. Several pioneering technical developments, such as methods to couple secondary ion mass spectrometry (SIMS) or ionoluminescence with the HIM, also offer the possibility for new and exciting research on biological materials. In this review, we present a comprehensive overview of almost all currently published literature which has demonstrated the application of HIM for imaging of biological specimens. We also discuss some technical features of this unique type of instrument and highlight some of the new advances which will likely become more widely used in the years to come.
Keywords: bio-imaging; flood gun; helium-ion microscopy; high resolution; HIM; HIM-SIMS; ionofluorescense

(untitled) - Ward, B. W.; Notte, J. A.; Economou, N. P. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2006)

(untitled) - Ward, B.; Notte, J. A.; Economou, N. P. (Photonics Spectra, 2007)

(untitled) - Notte, J.; Ward, B.; Economou, N.; Hill, R.; Percival, R.; Farkas, L.; McVey, S. (AIP Conf. Proc., 2007)

(untitled) - Scipioni, L.; Stern, L. A.; Notte, J.; Sijbrandij, S.; Griffin, B. (Adv. Mater. Processes, 2008)
Product code: ZAMP16606P27.

(untitled) - Joens, M. S.; Huynh, C.; Kasuboski, J. M.; Ferranti, D.; Sigal, Y. J.; Zeitvogel, F.; Obst, M.; Burkhardt, C. J.; Curran, K. P.; Chalasani, S. H.; Stern, L. A.; Goetze, B.; et al. (Sci. Rep., 2013)

(untitled) - Bell, D. C.; Erdman, N.; Jepson, M. A.; Rodenburg, C.; Inkson, B. J. (Microsc. Microanal., 2009)

(untitled) - Bell, D. (Microsc. Microanal., 2011)

(untitled) - Bazou, D.; Behan, G.; Reid, C.; Boland, J. J.; Zhang, H. Z. J. (J. Microsc. (Oxford, U. K.), 2011)

(untitled) - Bazou, D.; Santos-Martinez, M. J.; Medina, C.; Radomski, M. W. (Br. J. Pharmacol., 2011)

(untitled) - Arey, B.; Shutthanandan, V.; Orr, G. (Microsc. Microanal., 2011)

(untitled) - Boden, S. A.; Asadollahbaik, A.; Rutt, H. N.; Bagnall, D. M. (Scanning, 2012)

(untitled) - Boseman, A.; Nowlin, K.; Ashraf, S.; Yang, J.; LaJeunesse, D. (Micron, 2013)

(untitled) - Kim, K.-W. (Appl. Microsc., 2012)

(untitled) - Rice, W. L.; Van Hoek, A. N.; PÇunescu, T. G.; Huynh, C.; Goetze, B.; Singh, B.; Scipioni, L.; Stern, L. A.; Brown, D. (PLoS One, 2013)

(untitled) - Schürmann, M.; Frese, N.; Beyer, A.; Heimann, P.; Widera, D.; Mönkemöller, V.; Huser, T.; Kaltschmidt, B.; Kaltschmidt, C.; Gölzhäuser, A. (Small, 2015)

(untitled) - Leppänen, M.; Sundberg, L.-R.; Laanto, E.; de Freitas Almeida, G. M.; Papponen, P.; Maasilta, I. J. (Adv. Biosyst., 2017)

(untitled) - Sharma, A.; Schmidt, M.; Kiesel, B.; Mahato, N. K.; Cralle, L.; Singh, Y.; Richnow, H. H.; Gilbert, J. A.; Arnold, W.; Lal, R. (Front. Microbiol., 2018)

(untitled) - Said, N.; Chatzinotas, A.; Schmidt, M. (Adv. Biosyst., 2019)

(untitled) - Vinner, G. K.; Rezaie-Yazdi, Z.; Leppanen, M.; Stapley, A. G. F.; Leaper, M. C.; Malik, D. J. (Pharmaceuticals, 2019)

(untitled) - Veligura, V.; Hlawacek, G.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (J. Phys.: Condens. Matter, 2014)

(untitled) - Veligura, V.; Hlawacek, G.; Jahn, U.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (J. Appl. Phys., 2014)

(untitled) - Veligura, V.; Hlawacek, G.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (J. Lumin., 2015)

Scanning Ionoluminescence Microscopy with a Helium Ion Microscope - Franklin, T. M. W. (University of Southampton, 2012)

(untitled) - Sato, C.; Sato, M.; Ogawa, S. (Int. J. Mol. Med., 2018)

(untitled) - Dowsett, D.; Wirtz, T.; Vanhove, N.; Pillatsch, L.; Sijbrandij, S.; Notte, J. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2012)

(untitled) - Wirtz, T.; Vanhove, N.; Pillatsch, L.; Dowsett, D.; Sijbrandij, S.; Notte, J. (Appl. Phys. Lett., 2012)

Helium Ion Microscopy - Wirtz, T.; Dowsett, D.; Philipp, P. (SIMS on the Helium Ion Microscope: A Powerful Tool for High-Resolution High-Sensitivity Nano-Analytics, 2016)

(untitled) - Dowsett, D.; Wirtz, T. (Anal. Chem. (Washington, DC, U. S.), 2017)

Carl Zeiss Microscopy White paper: Multi-Modal Characterization with Secondary Ion Mass Spectrometry on ZEISS ORION NanoFab - Eyhusen, S.

(untitled) - Klingner, N.; Heller, R.; Hlawacek, G.; Facsko, S.; von Borany, J.; Wilhelm, R. A. (Patentschrift Ionenmikroskopievorrichtung, 2016)

Ionenstrahlanalytik im Helium-Ionen-Mikroskop - Klingner, N. (Universität Dresden, 2016)

(untitled) - Klingner, N.; Heller, R.; Hlawacek, G.; von Borany, J.; Notte, J.; Huang, J.; Facsko, S. (Ultramicroscopy, 2016)

Helium Ion Microscopy - Heller, R.; Klingner, N.; Hlawacek, G. (Backscattering Spectrometry in the Helium Ion Microscope: Imaging Elemental Compositions on the nm Scale, 2016)

(untitled) - Klingner, N.; Heller, R.; Hlawacek, G.; Facsko, S.; von Borany, J. (Ultramicroscopy, 2019)

(untitled) - Lovric, J.; Audinot, J.-N.; Wirtz, T. (Microsc. Microanal., 2019)

(untitled) - Kim, K. W. (Appl. Microsc., 2013)

Helium Ion Microscopy - Gölzhäuser, A.; Hlawacek, G. (HIM of Biological Samples, 2016)

Helium Ion Microscopy - Ward, B. (The ALIS Story, 2016)

Infection under the ion beam : focused ion beams and antibacterial properties of biomaterials - Leppänen, M. (University of Jyväskylä, 2020)

(untitled) - Inai, K.; Ohya, K.; Ishitani, T. (J. Electron Microsc., 2007)

(untitled) - Everhart, T. E.; Thornley, R. F. M. (J. Sci. Instrum., 1960)

Carl Zeiss Microscopy White Paper (2016): Zeiss ORION NanoFab

(untitled) - Tominski, C.; Lösekann-Behrens, T.; Ruecker, A.; Hagemann, N.; Kleindienst, S.; Mueller, C. W.; Höschen, C.; Kögel-Knabner, I.; Kappler, A.; Behrens, S. (Appl. Environ. Microbiol., 2018)

(untitled) - Meldrum, F. C.; Mann, S.; Heywood, B. R.; Frankel, R. B.; Bazylinski, D. A. (Proc. R. Soc. London, Ser. B, 1993)

(untitled) - Moreno-Osorio, J. H.; Benettoni, P.; Schmidt, M.; Stryhanyuk, H.; Schmitt-Jansen, M.; Pinto, G.; Pollio, A.; Frunzo, L.; Lens, P. N. L.; Richnow, H. H.; Esposito, G.; Musat, N. (FEMS Microbiol. Ecol., 2019)

(untitled) - Imlay, J. A. (Mol. Microbiol., 2006)

(untitled) - Rouault, T. A.; Tong, W.-H. (Nat. Rev. Mol. Cell Biol., 2005)

European Microscopy Congress 2016: Proceedings - Klingner, N.; Hlawacek, G.; Heller, R.; von Borany, J.; Facsko, S. (Nanometer Scale Time of Flight Back Scattering Spectrometry in the Helium Ion Microscope, 2016)

(untitled) - Pallon, J.; Yang, C.; Utui, R. J.; Elfman, M.; Malmqvist, K. G.; Kristiansson, P.; Sjöland, K. A. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1997)

(untitled) - Hell, S. W.; Wichmann, J. (Opt. Lett., 1994)

Development and biological applications of high-resolution ion beam induced fluorescense microscopy - Mi, Z. (National University of Singapore, 2015)

(untitled) - Breese, M. B. H.; Landsberg, J. P.; King, P. J. C.; Grime, G. W.; Watt, F. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1992)

(untitled) - Marshall, M. M.; Yang, J.; Hall, A. R. (Scanning, 2012)

(untitled) - Hall, A. R. (Microsc. Microanal., 2013)

(untitled) - Woehl, T. J.; White, R. M.; Keller, R. R. (Microsc. Microanal., 2016)

SRIM 2013 - The Stopping and Range of Ions in Matter - Ziegler, J. F.

(untitled) - Mousley, M.; Eswara, S.; De Castro, O.; Bouton, O.; Klingner, N.; Koch, C. T.; Hlawacek, G.; Wirtz, T. (Beilstein J. Nanotechnol., 2019)

npSCOPE

(untitled) - Zeitvogel, F.; Burkhardt, C. J.; Schroeppel, B.; Schmid, G.; Ingino, P.; Obst, M. (Geomicrobiol. J., 2017)

(untitled) - Loftus, A. F.; Joens, M. S.; Dunn, S. E.; Adams, M. W.; Huynh, C.; Goetze, B.; Fitzpatrick, J. A. J. (Microsc. Microanal., 2015)

(untitled) - Goetze, B.; Huynh, C.; Stern, L.; Wu, H.; Ferranti, D.; Ananth, M. (Microsc. Microanal., 2013)

(untitled) - Uryu, K.; Soplop, N.; Acehan, D.; Winer, B. Y.; Fischetti, V. A.; Sheahan, T.; Rice, C. M.; Hsu, M.; Robbiani, M.; Santulli, G.; Totary-Jain, H.; Goetze, B.; et al. (Microsc. Microanal., 2016)

(untitled) - Uryu, K.; Rice, C. M.; Catanese, M. T.; Santulli, G.; Totary-Jain, H.; Huynh, C.; Goetze, B. (Microsc. Microanal., 2017)

(untitled) - P unescu, T. G.; Shum, W. W. C.; Huynh, C.; Lechner, L.; Goetze, B.; Brown, D.; Breton, S. (Mol. Hum. Reprod., 2014)

(untitled) - Laufer, K.; Niemeyer, A.; Nikeleit, V.; Halama, M.; Byrne, J. M.; Kappler, A. (FEMS Microbiol. Ecol., 2017)

(untitled) - Bidlack, F. B.; Huynh, C.; Marshman, J.; Goetze, B. (Front. Physiol., 2014)

(untitled) - Tsuda, T.; Nemoto, N.; Kawakami, K.; Mochizuki, E.; Kishida, S.; Tajiri, T.; Kushibiki, T.; Kuwabata, S. (ChemBioChem, 2011)

(untitled) - Golding, C. G.; Lamboo, L. L.; Beniac, D. R.; Booth, T. F. (Sci. Rep., 2016)

(untitled) - Vanden Berg-Foels, W. S.; Scipioni, L.; Huynh, C.; Wen, X. J. (J. Microsc. (Oxford, U. K.), 2012)

(untitled) - Huyuan, C.; Marshman, J.; Dobeck, J.; Goetze, B.; Bidlack, F. B. (Microsc. Microanal., 2013)

(untitled) - Paunescu, T. G.; Breton, S.; Brown, D. (Physiol. News, 2014)

(untitled) - Tsuji, K.; Păunescu, T. G.; Suleiman, H.; Xie, D.; Mamuya, F. A.; Miner, J. H.; Lu, H. A. J. (Sci. Rep., 2017)

(untitled) - Herrera, M. G.; Pizzuto, M.; Lonez, C.; Rott, K.; Hütten, A.; Sewald, N.; Ruysschaert, J.-M.; Dodero, V. I. (Nanomedicine (N. Y., NY, U. S.), 2018)

(untitled) - Curtin, A. E.; Chiaramonti, A. N.; Sanders, A. W.; Ciesielski, P. N.; Chapple, C.; Mosier, N.; Donohoe, B. S. (Microsc. Microanal., 2014)

(untitled) - Bandara, C. D.; Singh, S.; Afara, I. O.; Wolff, A.; Tesfamichael, T.; Ostrikov, K.; Oloyede, A. (ACS Appl. Mater. Interfaces, 2017)

Characterisation of the bactericidal efficiancy of natural nanotopography using dragonfly - Bandara, C. C. D. I. M. (Queensland University of Technology, 2017)

(untitled) - Shahali, H.; Hasan, J.; Mathews, A.; Wang, H.; Yan, C.; Tesfamichael, T.; Yarlagadda, P. K. D. V. (J. Mater. Chem. B, 2019)

(untitled) - Belianinov, A.; Halsted, M. C.; Burch, M. J.; Songkil, K.; Retterer, S. T. (Microsc. Microanal., 2017)

(untitled) - Byrne, J. M.; Schmidt, M.; Gauger, T.; Bryce, C.; Kappler, A. (Environ. Sci. Technol. Lett., 2018)

(untitled) - Almeida, G. M. F.; Leppänen, M.; Maasilta, I. J.; Sundberg, L.-R. (Res. Microbiol., 2018)

(untitled) - Prasad, K.; Recek, N.; Zhou, R.; Zhou, R.; Aramesh, M.; Wolff, A.; Speight, R. E.; Mozetič, M.; Bazaka, K.; Ostrikov, K. (Sustainable Mater. Technol., 2019)

(untitled) - de Souza, W.; Attias, M. (J. Struct. Biol., 2015)

(untitled) - Gadelha, A. P. R.; Benchimol, M.; de Souza, W. (J. Struct. Biol., 2015)

(untitled) - de Souza, W.; Attias, M. (Exp. Parasitol., 2018)

(untitled) - Starr, M. P.; Seidler, R. J. (Annu. Rev. Microbiol., 1971)

(untitled) - Sockett, R. E. (Annu. Rev. Microbiol., 2009)

WHO priority pathogens list for Research and Development of new antibiotics

(untitled) - LeTourneau, M. K.; Marshall, M. M.; Thomashow, L. S.; Harsh, J. B. (Microsc. Microanal., 2015)

(untitled) - Kniggendorf, A.-K.; Gaul, T. W.; Meinhardt-Wollweber, M. (Microsc. Res. Tech., 2011)

Biogeochemical Cycles - Samuels, T.; Bryce, C.; Landenmark, H.; Marie‐Loudon, C.; Nicholson, N.; Stevens, A. H.; Cockell, C. (Microbial Weathering of Minerals and Rocks in Natural Environments, 2020)

(untitled) - Bryce, C.; Franz-Wachtel, M.; Nalpas, N. C.; Miot, J.; Benzerara, K.; Byrne, J. M.; Kleindienst, S.; Macek, B.; Kappler, A. (Appl. Environ. Microbiol., 2018)

(untitled) - Melton, E. D.; Swanner, E. D.; Behrens, S.; Schmidt, C.; Kappler, A. (Nat. Rev. Microbiol., 2014)

(untitled) - Nordhoff, M.; Tominski, C.; Halama, M.; Byrne, J. M.; Obst, M.; Kleindienst, S.; Behrens, S.; Kappler, A. (Appl. Environ. Microbiol., 2017)

(untitled) - Dohnalkova, A.; Arey, B.; Varga, T.; Miller, M.; Kovarik, L. (Microsc. Microanal., 2017)

(untitled) - Lybrand, R. A.; Austin, J. C.; Fedenko, J.; Gallery, R. E.; Rooney, E.; Schroeder, P. A.; Zaharescu, D. G.; Qafoku, O. (Sci. Rep., 2019)

(untitled) - Qafoku, O.; Lybrand, R. A.; Shutthanandan, V.; Gallery, R. E.; Austin, J. C.; Schroeder, P. A.; Fedenko, J.; Rooney, E.; Zaharescu, D. G. (Microsc. Microanal., 2019)

(untitled) - Rasa, K.; Heikkinen, J.; Hannula, M.; Arstila, K.; Kulju, S.; Hyväluoma, J. (Biomass Bioenergy, 2018)

(untitled) - LeTourneau, M. K.; Marshall, M. J.; Cliff, J. B.; Bonsall, R. F.; Dohnalkova, A. C.; Mavrodi, D. V.; Devi, S. I.; Mavrodi, O. V.; Harsh, J. B.; Weller, D. M.; Thomashow, L. S. (Environ. Microbiol., 2018)

(untitled) - Chen, S.-C.; Musat, N.; Lechtenfeld, O. J.; Paschke, H.; Schmidt, M.; Said, N.; Popp, D.; Calabrese, F.; Stryhanyuk, H.; Jaekel, U.; Zhu, Y.-G.; Joye, S. B.; et al. (Nature, 2019)

Advances in Imaging and Electron Physics - Hill, R.; Notte, J. A.; Scipioni, L. (Scanning Helium Ion Microscopy, 2012)

Helium Ion Microscopy - Shorubalko, I.; Pillatsch, L.; Utke, I. (Direct–Write Milling and Deposition with Noble Gases, 2016)

(untitled) - Vinner, G. K.; Richards, K.; Leppänen, M.; Sagona, A. P.; Malik, D. J. (Pharmaceutics, 2019)

(untitled) - Bandara, C. D.; Ballerin, G.; Leppänen, M.; Tesfamichael, T.; Ostrikov, K. K.; Whitchurch, C. B. (ACS Biomater. Sci. Eng., 2020)

(untitled) - Decelle, J.; Veronesi, G.; Gallet, B.; Stryhanyuk, H.; Benettoni, P.; Schmidt, M.; Tucoulou, R.; Passarelli, M.; Bohic, S.; Clode, P.; Musat, N. (Trends Cell Biol., 2020)

(untitled) - Chen, X.; Udalagama, C. N. B.; Chen, C.-B.; Bettiol, A. A.; Pickard, D. S.; Venkatesan, T.; Watt, F. (Biophys. J., 2011)

(untitled) - Sanders, A. W.; Jeerage, K. M.; Schwartz, C. L.; Curtin, A. E.; Chiaramonti, A. N. (Microsc. Microanal., 2014)

(untitled) - Reguera, G.; McCarthy, K. D.; Mehta, T.; Nicoll, J. S.; Tuominen, M. T.; Lovley, D. R. (Nature, 2005)

(untitled) - Stokes, D. J.; Mugnier, J.-Y.; Clarke, C. J. (J. Microsc. (Oxford, U. K.), 2004)